Indian Data Repositories in re3data: A Study - Mondal, Tanmay (Journal of Information and Knowledge, 2018)
A registry is a source of information. Registry of Research Data Repositories (re3data.org) is a global data registry for more than 1500 data repositories available in different academic disciplines worldwide. Different data repositories from India are listed in re3data. Majority of these data repositories are in scientific discipline. Most of the data repositories don’t follow any metadata standards for datasets. Only few provide permanent data links.